THE RELATIONSHIP OF MOTHER'S EDUCATION, JOB, AGE AND EDUCATION TO BABY MASSAGE - Ramayani (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Baby massage is a relaxation technique performed on babies and toddlers that has many benefits. Infant massage is great to help increase the baby's immune system, help relaxation, make it easier to sleep and help control fussiness and breathing. This study was conducted with the aim of knowing the relationship between mother's education, occupation, age and knowledge of infant massage. This study used quantitative research methods with a cross sectional research design. The study population consisted of 85 mothers and babies aged 1-12 months. The sampling method used the overall sampling method. The variables studied were presented in the form of frequency distribution tables, and tested using variance analysis and multiplication using a questionnaire tool. This research was conducted by TPMB Ririn Sevda Korini, SKM, S.Keb Tanjung Agung in July 2023. Data analysis was performed using Chi-square, univariate and bivariate statistical tests. Based on the results of univariate analysis, 40 (47.1%) respondents were well informed, out of 85 respondents who practiced baby massage, 56 (65%) respondents were well informed, 50 (58.8%) respondents were working, 48 (56.5%) respondents were old, and 40 (47%) respondents were highly educated. The results of bivariate analysis showed that there was a relationship between cognition and infant massage (p-value 0.023), between maternal employment and infant massage (p-value 0.033), age of mother and child massaged (p-value 0.02)3, value (p 0.041). There is a relationship between mother's education and infant massage (p-value 0.007).